Treatment of Parturition-Induced Rupture of Pubic Symphysis after Spontaneous Vaginal Delivery - C. Gräf; R. M. Sellei; S. Schrading; D. O. Bauerschlag (Case Reports in Obstetrics and Gynecology)
Parturition-induced rupture of pubic symphysis is an uncommon but severe complication of delivery. Characteristic symptoms are an immediate onset of suprapubic and/or sacroiliac pain within the first 24 hours postpartum, often accompanied by an audible crack. Diagnosis can be confirmed by imaging including X-ray, Magnet Resonance Imaging (MRI), and ultrasound. However, there is no consensus on the optimal therapy. Conservative treatment is predominantly used. It has been reported that, in cases of extreme symphyseal rupture with pelvic instability or persisting pain after conservative therapy, operative treatment achieves a successful outcome. In this report, we present a case of a twenty-year-old primigravida who developed suprapubic pain after a nonoperative vaginal birth with shoulder dystocia. A rupture of pubic symphysis with a gap of 60 mm was confirmed by means of X-ray and MRI. Simultaneously, other pelvic joint injuries could be excluded. Operative treatment by an open reduction and internal plate fixation yielded excellent results.